Assessment of water quality in the Garhwa and Palamu districts of Jharkhand - KUMAR, RAKESH; KARMAKAR, S; KUMAR, RAKESH; KOHLI, ANSHUMAN; DUTTA, S.; KUMARI, SWATI; MINZ, ASISAN (Journal of Soil and Water Conservation, 2020)
Surface and ground water samples collected from different locations (260) and sources of Garhwa and Palamu district of Jharkhand were analyzed for hydro-chemical properties namely BOD, COD, SAR and RSC. Water samples had pH and EC ranging between 6.69-8.48 and, 0.75-2.25 dSm-1, respectively. Carbonate, chloride and sulphate content of all the samples were within safe limit and suitable for drinking purpose. About 85% samples showed bicarbonate concentration above the safe limit. Over nearly 40% of the surface and ground water samples had nitrate concentration above the safe limit (45 mg/l) in Palamu district but it was on the lower side in Garhwa district. The extent of nitrate contamination in water samples of Garhwa district was comparatively low. Fluoride concentration in surface water was very low in both the districts. However, the open and bore well samples contained fluoride between 1.0 to 1.5 mg/l in 31.58 and 23.91% samples in Palamu district and in only 30.00 and 42.22% samples of Garhwa district. Thus fluoride concentration of water samples of Palamu district was unsafe (42 to 56%), while it was of a lower order (15 to 24%) in Garhwa district. Calcium, magnesium, potassium and sodium content in the drinking and irrigation water of Palamu and Garhwa districts were within the safe limit. The fluoride content of water was positively correlated with pH, calcium, magnesium, BOD, COD and RSC and negatively correlated with carbonate, bicarbonate and sulphate. The nitrate content of water was positively correlated with EC, bicarbonate, chloride, calcium and magnesium and negatively correlated with fluoride content.